A Brick-by-Brick Approach to Learning MIPS Microarchitecture - Yousafzai, Aimal (2023)
This paper presents a method for improving students' conceptual understanding of microarchitecture in a MIPS-based Computer Organization and Architecture course. The main goal of this course is for students to learn the functionality of the MIPS microprocessor, i.e., to understand the MIPS instruction set architecture (ISA) and its different microarchitectures (also known as organizations). In contrast to the traditional rote learning of microarchitecture, the proposed method, called the brick-by-brick approach, adopts jigsaw cooperative learning and modifies it specifically for learning microarchitecture. The proposed approach helps students to achieve significant gains in their understanding of microarchitecture concepts. A microarchitecture concept inventory is developed for this case study to assess students' concepts. The formats of concept inventory questions are very fluid and, as such, allow for easy modifications. Analysis of results and statistical tests demonstrate the benefits of the proposed method.